One-Week Dynamic Changes in Cardiac Proteomes After Cardiac Radioablation in Experimental Rat Model - Kim, Byoung Hyuck; Jung, Jin Woo; Han, Dohyun; Cha, Myung-Jin; Chang, Ji Hyun (Frontiers in Cardiovascular Medicine, 2022)
Background: Recently, stereotactic ablative radiotherapy (SABR) has been adopted to noninvasively treat catheter ablation-refractory ventricular tachycardia (VT). VT episodes have been dramatically reduced after SABR, within weeks; however the underlying mechanisms of these clinical effects and potential mediators of early anti-arrhythmic effect remain unclear. Methods: In this study, cardiac tissue was harvested from non-irradiated control (0 Gy), conventional irradiated control (2 Gy), and radioablative test (25 Gy) rat groups after 3 and 7 days of irradiation. The samples were proteomically analyzed to identify the differentially expressed proteins (DEP) between different groups. Validation experiments were performed similar to validation in profiling where Data independent acquisition and parallel reaction monitoring methods were used. Data are available via ProteomeXchange with identifier PXD030878. Results: Functional enrichment analysis of 25 Gy sample showed that among the downregulated proteins, “intracellular signal transduction” and “cell to cell adhesion” proteins were significantly affected at day 3 while “Ras protein signal transduction,” “GTPase regulation,” and “actin filament-based process” proteins were majorly affected at day 7. GO analysis demonstrated that most of the upregulated proteins belonged to the classes “cellular stress response,” “endomembranal organization,” or “endoplasmic reticulum stress response” at day 3. At day 7, 42 proteins, mainly associated with response to drug, organic substance, or radiation, were specifically upregulated in 25 Gy. DEP analysis of cardiac conduction showed Ryr2 and Cav1 upregulation and Cacna2d2, Gja3, Scnb2, and Kcnn3 downregulation in the 25 Gy group compared to 0 Gy. In validation experiments, four proteins (Gsta1, Myot, Ephx1, and Capg) were repeatedly detected with 25 Gy-specific patterns at day 7. Conclusions: 25 Gy single fractional irradiation induces considerable cardiac proteome changes within the first 7 days, distinct from 2 Gy. Several candidate proteins displayed 25 Gy-specific changes and were related to oxidative stress-induced innate response or cardiac remodeling processes. Future studies should explore the specific role of these proteins upon cardiac radioablation.